A Flint Hills Legacy: Grass and Cattle - Jane Koger (Symphony in the Flint Hills, 2016)
When Ezra Beedle homesteaded land in the Flint Hills in the 1800s, he saw a vast sea of tallgrass prairie with wide-open spaces and few trees.
Keywords: homesteaded; tallgrass prairie; conservation; hunting; fishing; hiking; partnership; ranchers; MAJESTIC HILLS; Allan Chow; FLYING J; Don Wolfe